1987
DOI: 10.1073/pnas.84.7.1969
|View full text |Cite
|
Sign up to set email alerts
|

Polysialic acid units are spatially and temporally expressed in developing postnatal rat kidney.

Abstract: We report the presence of a(2--8)-linked polysialic acid as detected with a monoclonal antibody outside the nervous tissue in the postnatal developing rat kidney. By immunoblot analysis, the reactivity was confined to a broad band of apparent molecular mass 200-250 kDa. By immunohistochemistry, the polysialic acid units were found throughout the ureteric bud-derived collecting duct system. In developing nephrons derived from the metanephrogenic mesenchyme, polysialic acid units were only regionally and transie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
64
0

Year Published

1991
1991
2007
2007

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(68 citation statements)
references
References 36 publications
(33 reference statements)
4
64
0
Order By: Relevance
“…Additionally, there is increasing evidence that polysialic acid, which in the embryo is exclusively associated with NCAM (Cremer et al, 1994;Ono et al, 1994) and is abundantly expressed in the developing postnatal rat kidney (Roth et al, 1987), and influences neuronal outgrowth and pathfinding (Landmesser et al, 1990;Tang et al, 1992;Zhang et al, 1992), migration of subependymal cells (Tomasiewicz et al, 1993), and reorganization of myotubes (Fredette et al, 1993). See Rutishauser (1992) for a review of NCAM polysialic acid.…”
mentioning
confidence: 99%
“…Additionally, there is increasing evidence that polysialic acid, which in the embryo is exclusively associated with NCAM (Cremer et al, 1994;Ono et al, 1994) and is abundantly expressed in the developing postnatal rat kidney (Roth et al, 1987), and influences neuronal outgrowth and pathfinding (Landmesser et al, 1990;Tang et al, 1992;Zhang et al, 1992), migration of subependymal cells (Tomasiewicz et al, 1993), and reorganization of myotubes (Fredette et al, 1993). See Rutishauser (1992) for a review of NCAM polysialic acid.…”
mentioning
confidence: 99%
“…Glycoproteins can also be modified by linear homopolymers of ␣2-8-linked sialic acid with a degree of polymerization greater than seven that are referred to as polysialic acid (PSA) 3 (2). Expression of PSA is great during ontogeny and is drastically reduced in the adult, where mostly neuroectoderm-derived tissue contains PSA (2)(3)(4)(5). Polysialic acid has been identified in only five mammalian proteins: NCAM, CD36, ␣-subunit of the voltagegated sodium channel, and two sialyltransferases, ST8Sia II and ST8Sia IV (2, 6 -9).…”
mentioning
confidence: 99%
“…This conclusion is based on several observations: (a) the enzymatic hydrolysis of sialic acid from DPP IV, as well as the presence of sialic acid and wheat germ agglutinin in the competitive ELISA, abolished the reactivity of this monoclonal antibody; (b) this epitope is no longer expressed in primary hepatocytes treated with deoxymannojirimycin; (c) the first appearance of epitope D in the Golgi apparatus and increased occurrence in the plasma membranes. The application of free-flow electrophoresis for subfractionation of the Golgi apparatus cisternae showed that epitope D became primarily part of DPP IV in truns most cisternae, correlating to the exhibited translocation of both galactosyltransferase and sialyltransferase in the Golgi apparatus of rat liver (Morre el al., 1984;Taatjes et al, 1987). Immunohistochemical studies of various rat organs revealed reactivity with this antibody in intestinal goblet cells and in postnatally developing collecting duct cells of the kidney, while neither DPP IV enzyme activity nor reactivity with any other antibody were observed at these sites (Hartel et al, 1988b;Hartel-Schenk et al, 1990).…”
Section: Discussionmentioning
confidence: 94%
“…In contrast to other parts of the intestinal mucosa goblet cells express sialyltransferase activity in their trans Golgi cisternae (Roth et al, 1986). In the developing kidney the presence of cr2,X-linked poly(sia1ic acid) has been reported throughout the collecting duct system (Roth et al, 1987). The monoclonal antibody against the epitope D, however, cannot distinguish between a2,3-, a2,6-and a2,8-linked sialic acid.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation